Makna Kata Petra dalam Matius 16:18 dan Hubungannya terhadap Fondasi Gereja - Misael Widodo; Nenny Natalina Simamora; Aeron Frior Sihombing (Sekolah Tinggi Teologi SAPPI Ciranjang, 2016)
The word petra in Matthew 16:18 become the most controversial debates in interpretation of the New Testament. There is a group who interpreted petra as Peter and the others interpreted as Jesus. In addition, petra is also interpreted as Peter’s confession of faith, all believers and includes all of the exiting interpretation. But the most incisived debate is whether petra means Peter or Jesus. This involves the interpretation of Roman Catholic and Protestant, as this will have an impact on the understanding of who was the first foundation of the Church. The main problem, who is meant by the word petra in Matthew and how his relationship to the foundation of the Church. Subject matter is examined in depth by using descriptive method of grammatical historical approach.. Based on the study, petra means Peter was the first stone as the foundation selected and placed by Jesus to build His Church.